2017
DOI: 10.5935/2318-7670.v05nespa16
|View full text |Cite
|
Sign up to set email alerts
|

Coeficiente de rendimento em madeira serrada de oito espécies nativas de Mato Grosso

Abstract: Recebido em dezembro/2016; Aceito em abril/2017. RESUMO:A pesquisa foi desenvolvida em uma serraria no norte de Mato Grosso e teve como objetivo, avaliar o rendimento em madeira serrada de oito espécies nativas, tradicionalmente utilizadas na indústria de processamento mecânico no estado. Na indústria selecionaram-se aleatoriamente, 6 toras de cada uma das 8 espécies nativas escolhidas, totalizando 48 toras para o desenvolvimento do estudo. A metodologia empregada foi conforme prescrita na Resolução nº 411 do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Conicity has a direct influence on the final yield of wood from logs and has been cited as one of the principal factors responsible for low yields in Amazonian sawmills (Garcia et al, 2012;Mendoza et al, 2017;Lima et al, 2019). In the present study, in spite of using estimated values for percent volumetric yield, effects of conicity are possibly present with respect to yield of wood.…”
Section: Conicity and Yield By Speciesmentioning
confidence: 69%
“…Conicity has a direct influence on the final yield of wood from logs and has been cited as one of the principal factors responsible for low yields in Amazonian sawmills (Garcia et al, 2012;Mendoza et al, 2017;Lima et al, 2019). In the present study, in spite of using estimated values for percent volumetric yield, effects of conicity are possibly present with respect to yield of wood.…”
Section: Conicity and Yield By Speciesmentioning
confidence: 69%
“…In practice, the Amazon timber industry uses a low technological apparatus in their sawmills and generates a considerable amount of wood waste that is discarded. Sawmills are limited to meeting the demand of their buyers' orders to remain competitive in the market (Mendonza et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Several variables influence sawmill performance, including the characteristics of the timber species being processed, the cutting machinery used, and the diameter and quality of the logs (Marchesan et al 2014;Danielli et al 2016;Mendonza et al 2017;Romero et al 2020). Together, these factors make it difficult to calculate an accurate generalized ratio of original volume of logs entering the system, and the final volume of processed wood that leaves it.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the importance of this factor, many authors have inferred the sawn yield of Amazon wood industries, as in the works of Gerwing et al (2001) [5], Veríssimo et al (2002) [6], and Lentini et al (2005) [7]. Nascimento et al (2006) [8] presented sawn yields between 32% and 41% for the industries of the State of Pará, Brazil, while the recent works of de Mendoza Borges et al (2017) [9] and Melo et al (2019) [10] showed an average lumber yield of 47.7% for the Amazon region. Recently, da Silva Luz et al (2021) [4] inferred an average lumber yield of 45% for the State of Pará and mentioned the prospect of the energy potential of wood residues.…”
Section: Introductionmentioning
confidence: 99%